Incidental Gallbladder Cancer after Laparoscopic Cholecystectomy for Cholelithiasis, and Factors Affecting the Prognosis: A Single-center Experience - Süleyman Demiryas; Ozan Akıncı; Nuray Kepil; İhsan Taşçı (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:Despite surgical and radiological innovations, gallbladder cancer (GC) is usually diagnosed incidentally by the pathological examination of the cholecystectomy specimens, and it is defined as incidental GC (IGC).Methods:Medical files of patients, who underwent cholecystectomy, were analyzed retrospectively. We investigated the relationship between clinicopathological features and survival in patients with IGC.Results:We performed cholecystectomy surgery in 6225 patients in 20 years. Only 21 patients with IGC were included in this study. The distribution of the tumor stages was as follows: in situ cancer (n=1), T1 (n=2), T2 (n=7), and T3 (n=11). Tumor subtypes were identified as adenocarcinoma (n=16), neuroendocrine tumor (n=2), mucinous carcinoma (n=2), and adenosquamous carcinoma (n=1). Advanced ‘‘T stage’’, conversion of laparoscopic cholecystectomy to open cholecystectomy (OCC), positive surgical margins, positive lymphovascular invasion and increased levels of pre-operative alkaline phosphatase (ALP) were found to be associated with poor survival.Conclusion:In case of OCC or high preoperative ALP activity in cholelithiasis, IGC should be kept in mind. Pathology report on IGC should give information on all histopathological prognostic features in order to avoid loss of time associated with re-examination of specimens due to absence of sufficient information in the initial pathology report and enable the surgical team to perform re-operation for T1b tumors or more advanced IGC in a timely fashion.